Physiological predictors of flat-water kayak performance in women - Bishop, D. (European Journal of Applied Physiology, 2000)
This study was conducted to investigate the relationship between selected physiological variables and 500-m flat-water kayak (K500) performance. Nine female, high-performance kayak paddlers, mean (SD) age 23 (5) years, participated in this investigation. Testing was conducted over 6 days and included anthropometric measurements (height, body mass and skinfolds), an incremental test to determine both peak V˙O2 and the "anaerobic threshold" (Than), and a 2-min, all-out test to calculate accumulated oxygen deficit (AOD). Blood lactate concentrations were measured during the incremental test and at the completion of both tests. Subjects also completed a K500 race under competition conditions. K500 time was significantly correlated with both peak V˙O2 (r=-0.82, P < 0.05) and the power output achieved at the end of the incremental test (r=-0.75, P < 0.05). However, the variable most strongly correlated with K500 time was Than (r=-0.89, P < 0.05). A stepwise multiple regression, for which r=0.95 and the standard error of estimate=1.6 s, yielded the following equation: K500time(s)=160.60.154×AOD·kg-1 -0.250 × Than. In conclusion, the results of this study have demonstrated that although K500 performance is a predominantly aerobic activity, it does require a large anaerobic contribution. The importance of both the aerobic and anaerobic energy systems is reflected by the K500 time being best predicted by a linear combination of Than and AOD · kg-1. This suggests the need to develop and implement training programmes that develop optimally both of these physiological attributes. Further research is required to elucidate the most effective means by which to develop both the aerobic and anaerobic energy systems.